Competitiveness: from a misleading concept to a strategy supporting Beyond GDP goals. Issue 5 (19th October 2015) - Aiginger, Karl; Vogel, Johanna
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to show how the term competitiveness has been applied and adapted since Michael Porter made it respectable in economics, strategic management and consulting. This paper connects the concept with new developments in the theory of the firm, theories of growth and, finally, with Beyond GDP literature. Design/methodology/approach – This paper distinguishes between input and output competitiveness, developing a set of indictors for both. Countries are ranked according to costs, structure and capabilities (drivers of competitiveness) as well as according to economic, social and ecological performance (performance pillars). Finally, outcome competitiveness is explained by the individual drivers, using econometrics and principal component analyses. Practical implications – Defining competitiveness as the ability of a country or nation to deliver Beyond GDP goals changes the policy conclusions drawn from the quest for competitiveness. Policies to reduce costs prove inferior relative to "high-road strategies" built on skills, innovation and supporting institutions. Ecological ambition and social investment are not costs, but enablers of competitiveness for high-income countries. Originality/value – Connecting the well-known term competitiveness with Beyond GDP goals is a new approach. It is very different from the old concept of cost competitiveness criticized heavily by Paul Krugman. Supplying a set of indicators to measure "low-road" and "high-road" competitiveness leads to important new policy conclusions.